A novel In vitro model of blast traumatic brain injury - Campos,Pires R; Yonis,A; Macdonald,W; Harris,K; Edge,C; Mahoney,P; Dickinson,R (Jove-Journal of Visualized Experiments, 2018)
Traumatic brain injury is a leading cause of death and disability in military and civilian populations. Blast traumatic brain injury results from the detonation of explosive devices, however, the mechanisms that underlie the brain damage resulting from blast overpressure exposure are not entirely understood and are believed to be unique to this type of brain injury. Preclinical models are crucial tools that contribute to better understand blast-induced brain injury. A novel in vitro blast TBI model was developed using an open-ended shock tube to simulate real-life open-field blast waves modelled by the Friedlander waveform. C57BL/6N mouse organotypic hippocampal slice cultures were exposed to single shock waves and the development of injury was characterized up to 72 h using propidium iodide, a well-established fluorescent marker of cell damage that only penetrates cells with compromised cellular membranes. Propidium iodide fluorescence was significantly higher in the slices exposed to a blast wave when compared with sham slices throughout the duration of the protocol. The brain tissue injury is very reproducible and proportional to the peak overpressure of the shock wave applied.